Analisis Tingkat Kepuasan Mahasiswa terhadap Kualitas Pelayanan Universitas Muhammadiyah Tasikmalaya - endah nur mahmudah; Rissa Nuryuniarti (Entrepreneurship Faculty, Universitas Garut, 2019)
This study aims to determine the level of student satisfaction with the quality of service at Muhammadiyah University of Tasikmalaya by looking for service dimensions that affect student satisfaction. The method used is multiple linear regression analysis using total sampling technique, namely the entire population is the object of research. The population in this study were all 4th semester UMTAS students. The process of collecting data applies ICT (information and communication technology). In this case the distribution and filling out of the questionnaire utilizes Googleform, which is a very easy and efficient data collection tool from Google. The researcher only informs the address of the shortlink that has been made, namely bit.ly/2WZtLr7 to the respondent, and the respondent can access the link from their respective Android cellphones. The results of the study show that simultaneously the five variables have a positive and significant effect on student satisfaction, with a coefficient of determination (R2) of 0.868. That is the five independent variables effect the student satisfaction variable by 86.8% while the rest (13.2%) is influenced by other variables not examined in this study.